Modelling and performance analysis of FFR‐aided two layer aerial‐terrestrial network. Issue 5 (1st March 2020) - Saluja, Deepak; Kumar, Suman
Abstract : Exploiting aerial base stations (A‐BSs) in conjunction with terrestrial base stations (T‐BSs) is an effective solution to provide uniform coverage everywhere, and anytime. However, the addition of A‐BSs in an existing terrestrial network would intensify the inter‐cell interference to user equipment, leads to a degraded signal‐to‐interference‐ratio. There is a need to exploit inter‐cell‐interference‐coordination (ICIC) scheme in such aerial‐terrestrial network. Further, the aerial‐terrestrial network requires a multi‐layer environment to be modelled in many scenarios. In this study, the authors propose fractional frequency reuse (FFR) scheme as an ICIC scheme for two‐layer aerial‐terrestrial network. The analytical expression of coverage probability and average rate are derived for the proposed scheme, and compare it with the scheme, where no ICIC is considered in aerial‐terrestrial network, and conventional scheme, where only T‐BSs are considered. It is shown that the proposed scheme outperforms the no ICIC scheme and conventional scheme. Simulation results are shown to support their analytical results.